Protein hidrolisat daging bekicot (Achatina fulica) sebagai pengurang penggunaan tepung ikan terhadap performa ayam kampung super - Ujang Suryadi; Shokhirul Imam; Aufa Fariza Ahmad (Jurnal Ilmu Peternakan Terapan, 2021)
The aim of the study was to determine the level of use of fermented snail meat protein hydrolyzate (FSMPH) as a reduction of fish meal (FM) in the ration, and its effect on the production performance of “super” native chicken (SNC). Research materials were SNC unsexing and FSMPH. The study used an experimental method with a completely randomized design with 5 treatments and 4 replications. The research ration treatments included P0 = FM 8% without FSMPH (Control), P1= FM 6%+FSMPH 5 ml/kg ration, P2= FM 4%+FSMPH 10 ml/kg ration, P3= FM 2%+FSMPH 15 ml/kg ration, P4= FM 0%+FSMPH 20 ml/kg ration. Research rations began to be applied to chickens aged 2 days old until the harvest was 60 days old. The results showed that the a reduction of FM with FSMPH on SNC ration consumption at each level had no significant effect (P>0.05) but presented a significant difference (P<0.05) on lower final body weight, lower ADG and higher FCR, especially for treatment P4 with a FSMPH level of 20 ml/kg of feed. The conclusion was that FSMPH usage up to 75% can be used to reduce the FM percentage in the ration as much as 8%.